Laser de baixa intensidade e scaffold de Biosilicato®: efeitos isolados e da associação das duas modalidades terapêuticas no reparo ósseo - Rossi, Karina Nogueira Zambone Pinto (Universidade Federal de São Carlos, 2011)
This study aimed to evaluate the effects of low intensity laser therapy (LLLT) (830nm, 120J/cm2, 100mW) and implantation of Biosilicate® scaffolds, associated or not, in histological aspects, biomechanical properties of the bone callus and immunoexpression of proteins, growth and transcription factors related to different stages of bone repair, at 15, 30 and 45 days after surgery of bone defects induced in the tibia.of rats. For this, three studies were performed in which a total of one hundred and twenty male Wistar rats (3 months ± 280 g) were submitted to bilateral tibial defects and randomly distributed in four experimental groups with 30 animals each. In the first study the effects of the implantation of Biosilicate® scaffolds in bone defects of rats were investigated in two groups: bone defect group (GC) and bone defect treated with Biosilicate® scaffold group (GB). The implantation of the scaffold was performed subsequent to surgery of bone defect. Histological analysis revealed that animals of GB showed newly formed bone better organized at 30 and 45 days after surgery. The immunohistochemical analysis demonstrated that the Biosilicate® scaffold promoted a higher expression of COX-2 on days 15 and 30 after surgery, immunostaining positive of RUNX-2 in all periods, increased expression of RANKL on day 15 and positive immunoexpression of BMP-9 on the 45th day. However, the Biosilicate® scaffold did not increase the mechanical properties of bone callus. Thus, the implantation of Biosilicate® scaffold was effective in stimulating the repair of tibial defects, however, was not able to improve their mechanical properties. In the second study, the spatialtemporal changes in the process of bone healing in defects treated with LLLT were evaluated in two groups: GC and bone defect treated with laser group (GL). The laser treatment started immediately following the surgery of bone defects and have been 8, 15 or 23 sessions with an interval of 48 hours between them. The histological and morphometric analysis revealed that the GL showed better tissue organization at 15 and 30 days after surgery, and biggest area of newly formed bone at day 15. The immunohistochemistry showed that the LLLT promoted higher expression of COX-2 at day 15, immunostaining of RUNX-2 positive in all periods, higher immunoexpression of BMP-9 on day 30 and higher immunoreactivity of RANKL at day 15. However, the LLLT did not increase the biomechanical properties of bone callus. Thus, the LLLT improved the process of bone healing, but was unable to improve its biomechanical properties. In the third study the effects of the association of LLLT with implants of Biosilicate® scaffolds in bone healing were investigated in three experimental groups: GC, GB and Biosilicate® scaffold irradiated with laser group (GBL). The implantation of the scaffold was performed following the surgery of bone defect. The laser treatment started immediately after surgery and were performed 8, 15 or 23 sessions with an interval of 48 hours between them. At 15 days after surgery, the histological analysis revealed granulation tissue and newly formed bone juxtaposed to the surface of scaffolds in GB and GBL. Thirty days after injury, the GB and GBL had better organized newly formed bone compared to the CG. At day 45 was possible to observe granulation tissue in the defects of the GBL. In the GB, the peak of immunoexpression of COX-2 occurred on the 15th day and in the GBL, on the 30th day. The GB and GBL showed positive immunoexpression of BMP-9 up to 45th day after surgery, while RANKL immunoexpression was higher in the GBL at day 30. However, 30 and 45 days after injury, the animals of GB and GBL showed statistically lower values of maximum load compared to the CG. Thus, the association of the scaffold Biosilicate® with laser irradiation has osteogenic activity during the bone repair, however, the scaffold Biosilicate® associated or not with the laser irradiation is not effective to improve mechanical properties of the bone callus. Finally, we concluded that LLLT (λ = 830 nm, 120J/cm2) and implantation of Biosilicate® scaffolds, associated or not, were effective to stimulate the bone consolidation by improving the development of newly formed bone and activating immunoexpression of proteins, growth and transcription factors related to different stages of bone healing in tibial defects in rats. However, these therapeutic modalities associated or not, were unable to improve mechanical properties of the bone callus.
Keywords: Biotecnologia; Laser de baixa intensidade; Tecido ósseo; Ossos - fratura; Histologia; Biomecânica; Reparo ósseo; Biosilicato®; Scaffold de biomaterial; Terapia laser de baixa intensidade; Estudo in vivo.; Bone repair; Biosilicate®; Biomaterial scaffold; Low level laser therapy, In vivo study; CIENCIAS BIOLOGICAS::MORFOLOGIA::HISTOLOGIA